Development and validation of a stability-indicating isocratic reverse phase-liquid chromatography assay for determination of phenytoin in bulk and pharmaceutical formulations - Teo, S.Y.; Rathbone, M.J.; Coombes, A.G.A.; Lee, S.Y.; Gan, S.N. (Innovare Academics Sciences Pvt. Ltd, 2015)
Objective: To develop and validate a stability-indicating reversed phase high performance liquid chromatography (RP-HPLC) assay for the determination of phenytoin in bulk and pharmaceutical dosage forms. Methods: A HPLC instrument incorporating aZorbaxC-18 analytical column (250x4.6 mm, 5μm particles) with a mobile phase comprising acetonitrile: water in the ratio 50:50 (%v/v) was employed for the determination of phenytoin. The flow rate was set with an isocratic program, the temperature of the column was maintained at 25 °C and a detection wavelength of 200 nm was employed using an ultraviolet detector. The method was validated as per The International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) guidelines. Results: Total chromatographic analysis time per sample was 6 min with phenytoin eluting with the reaction time of 4.6±0.2 min. Phenytoin was exposed to acidic, basic, oxidative, photolytic and thermal stress conditions and the specificity of the assay was confirmed. The calibration plot was linear (R2≥0.999) over the phenytoin concentration range 5.0-100.0μg/ml. The percentage means recoveries were found to be in the range of 98- 102%. The relative standard deviation of precision and robustness were within prescribed limits (<2%). The limit of detection was 0.047 μg/ml while the limit of quantitation was established as 0.143 μg/ml. Conclusion: A simple, accurate, precise and stability-indicating RP-HPLC assay was successfully developed for the determination of phenytoin in bulk and dosage forms. Hence, this assay is useful for the analysis of phenytoin in formulations in medicines development and pharmaceutical manufacturing setting.